Survey Penerapan Kurikulum 2013 Pada Mata Pelajaran Penjas Di Sekolah Menengah Pertama Negeri : (Survey on the Implementation of the 2013 Curriculum in Physical Education Subjects at Public Middle Schools) - GioFani Pangaribuan Pangaribuan; Rifqi Aufan (Jurnal Ilmu Olahraga dan Kepelatihan Indonesia, 2020)
This study aims to determine the extent of the application of the 2013 curriculum in Physical Education subjects in the State Junior High Schools in Medan Tembung District. This research was conducted in Medan Tembung Subdistrict in 2019. The population in this study was the Public Middle School Physical Education Teacher in Medan Tembung Subdistrict. The sample in this study is total sampling which is the same as the population that is the Public Middle School Physical Education teacher in the District of Medan Tembung. Data collection techniques used are using survey techniques. Data were analyzed using quantitative descriptive analysis techniques. The results of this study indicate that: the average percentage of curriculum application in the State Junior High Schools in Medan Tembung District, for SMP Negeri 27 in the "Good" category, with an average percentage of 75.33%, then for SMP Negeri 35 also in the "Good" category with an average percentage of 78.00%, After that for SMP Negeri 17 also in the "good" category, with an average percentage of 75.55%, and in SMP Negeri 29 also in the "good" category "With an average percentage of 78.88%, after that in MTSN 2 it is also in the" good "category with an average percentage of 79.55%. Abstrak. Penelitian ini bertujuan untuk mengetahui Sejauh Mana Penerapan Kurikulum 2013 Pada Mata Pelajaran Penjas di Sekolah Menengah Pertama Negeri Se-Kecamatan Medan Tembung. Penelitian ini dilaksanakan di Kecamatan Medan Tembung tahun 2019. Populasi dalam penelitian ini adalah Guru Penjas Sekolah Menengah Pertama Negeri di Kecamatan Medan Tembung. Sampel dalam penelitian ini total sampling yakni sama dengan populasi yaitu guru penjas Sekolah Menengah Pertama Negeri di Kecamatan Medan Tembung. Teknik pengumpulan data yang digunakan adalah menggunakan teknik survei. Data dianalisis menggunakan teknik analisis deskriptif kuantitatif. Hasil penelitian ini menunjukkan bahwa: rata-rata persentase Penerapan Kurikulum di Sekolah Menengah Pertama Negeri Se-Kecamatan Medan Tembung, untuk SMP Negeri 27 dalam kategori â€œBaikâ€, dengan persentase rata-rata sebesar 75,33%, Kemudian untuk SMP Negeri 35 juga dalam kategori â€œBaikâ€ dengan presentase rata-rata sebesar 78,00%, Setelah itu untuk SMP Negeri 17 juga dalam kategori â€œbaikâ€, dengan persentase rata-rata sebesar 75,55%, Dan di SMP Negeri 29 juga dalam kategori â€œbaikâ€ dengan persentase rata-rata 78,88%, Setelah itu di MTSN 2 juga dalam kategori â€œbaikâ€ dengan persentasu rata-rata 79,55%.